Thread Displacement and Intensity Oscillations in a Quiescent Prominence - Yuxiang Song; Zongjun Ning; Dong Li; Fanpeng Shi; Jun Xu; Yuzhi Yang (The Astrophysical Journal)
In this paper, we investigate the thread displacement and intensity oscillations in a quiescent prominence observed by New Vacuum Solar Telescope at the H α line center on 2019 October 31. Each individual thread is traced by the local maximum intensity among its width at various times. In total, 35 threads are detected at six heights parallel to the solar surface. We find 29/35 threads exhibiting the displacement oscillation. A sinusoidal function is used to fit them, and a mean period of 26 minutes is identified. By slicing the same thread at different positions, we find that the oscillation of the thread is very likely a standing wave, but it could also be a long-wavelength propagating wave. After integrating the intensity along the thread width, we also find 8/35 threads presenting their intensity oscillation with a mean period of 7.7 minutes. In total, 7/35 threads exhibit both the displacement and the intensity oscillations.